Astrocytes in (Patho)Physiology of the Nervous System - Vladimir Parpura, Philip G. Haydon. (Springer, 2017)
Astrocytes were the original neuroglia that Ramón y Cajal visualized in 1913 using a gold sublimate stain. This stain targeted intermediate filaments that we now know consist mainly of glial fibrillary acidic protein, a protein used today as an astrocytic marker. Cajal described the morphological diversity of these cells with some astro-cytes surrounding neurons, while the others are intimately associated with vasculature.